Identification of microRNA associated with the elimination of hepatitis C virus genotype 1b by direct‐acting antiviral therapies. Issue 4 (20th September 2020) - Yoneyama, Hirohito; Morishita, Asahiro; Iwama, Hisakazu; Fujita, Koji; Masaki, Takahiro; Tani, Joji; Tadokoro, Tomoko; Nomura, Takako; Sakamoto, Teppei; Oura, Kyoko; Takuma, Kei; Nakahara, Mai; et al.
Abstract: Background and Aim: Direct‐acting antiviral (DAA) therapies have been proven to be highly effective for the eradication of hepatitis C virus (HCV) without resistance‐associated substitutions (RASs). However, even in cases with no detected RASs, treatment sometimes fails, suggestive of the existence of some host‐related factors involved in HCV eradication by DAAs. To explore such factors, we analyzed the serum microRNAs (miRNAs) of patients who received DAA treatment. Methods: The serum miRNA expression levels of 39 patients with chronic HCV infection without any detectable RASs, who achieved sustained virological response with asunaprevir/daclatasvir or grazoprevir/elbasvir therapy, were investigated cyclopedically, using oligonucleotide microarrays. The effects of specific miRNAs on the replication of HCV were measured in the HCV genomic replicon containing Huh‐7 hepatoma cells. Results: Along with the disappearance of HCV, the expression quantiles of 16 miRNAs in the asunaprevir/daclatasvir group and 18 miRNAs in the grazoprevir/elbasvir group showed a tendency to increase or decrease. Among these molecules, adjustments for multiple testing yielded a significant differential expression at a false discovery rate of less than 5% for only one molecule, hsa‐miR‐762. Its expression quantile increased after HCV exclusion in all patients who had achieved sustained virological response. Quantitative polymerase chain reaction analysis validated a significant increase in the serum hsa‐miR‐762 after disappearance of HCV. On the contrary, hsa‐miR‐762 was decreased in the relapse and breakthrough of HCV in DAA failures. Transfection of hsa‐miR‐762 into cultured HCV‐infected hepatocytes significantly decreased HCV‐RNA replication. Conclusion: These data suggest that hsa‐miR‐762 is one of the host factors participating in HCV exclusion by DAA therapy.